Pedagogia de Projetos: uma experiência na educação infantil - Lobato, Valéria Oliveira dos Santos; Alves, Maria Cristina S. de Oliveira; Fratari, Maria helena Dias (Olhares & Trilhas, 2011)
Pedagogia de Projetos: uma experiência na educação infantil